1996
DOI: 10.3109/00365599609181300
|View full text |Cite
|
Sign up to set email alerts
|

Blood Loss in Long-Term Aspirin Users Undergoing Transurethral Prostatectomy

Abstract: As aspirin is now widely used for preventing recurrence of cardiovascular and cerebrovascular disorders, many men selected for transurethral resection of the prostate (TURP) are aspirin users. The previous indication for aspirin as a preoperatively administered antithrombotic agent is no longer common. In this study we investigated the blood loss in long-term aspirin users (250 mg/day) undergoing TURP. The mean blood loss in the 40 aspirin users was 358 (range 50-1550) ml, and in a control group of 42 men it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…However, in our study we did not observe any difference in postoperative bleeding events between NSAID and the control group. This is consistent with previous studies that demonstrated a low incidence of postoperative bleeding with the use of NSAIDs when compared with narcotic analgesia after TURP (8)(9)(10)(11)(12). In a meta-analysis of 1,368 patients undergoing tonsillectomy, Krishna et al reported that the incidence of postoperative bleeding was not affected by NSAID consumption (9).…”
Section: Commentssupporting
confidence: 79%
“…However, in our study we did not observe any difference in postoperative bleeding events between NSAID and the control group. This is consistent with previous studies that demonstrated a low incidence of postoperative bleeding with the use of NSAIDs when compared with narcotic analgesia after TURP (8)(9)(10)(11)(12). In a meta-analysis of 1,368 patients undergoing tonsillectomy, Krishna et al reported that the incidence of postoperative bleeding was not affected by NSAID consumption (9).…”
Section: Commentssupporting
confidence: 79%
“…Based on these studies, discontinuation of ASA before the surgical intervention was recommended. Ala-Opas et al found by comparison of 40 patients under ASA versus 42 patients without oral platelet inhibition no difference in the average blood loss and thus saw no contradictions for TURP under ASA (11).…”
Section: Discussionmentioning
confidence: 99%
“…These early studies therefore recommended the withdrawal of non-steroidal anti-inflammatory drugs one week before TUR-P. This recommendation was challenged by studies showing no significant increase in blood loss if patients were taking aspirin [28,29]. However, a higher incidence of late bleeding with tamponade of the urinary bladder requiring emptying in the operating room was found [29].…”
Section: Hemorrhagic Risks In Urologic Surgerymentioning
confidence: 99%
“…This recommendation was challenged by studies showing no significant increase in blood loss if patients were taking aspirin [28,29]. However, a higher incidence of late bleeding with tamponade of the urinary bladder requiring emptying in the operating room was found [29]. A randomized controlled study found that patients taking 150 mg aspirin showed no difference in intraoperative hemorrhage, operation time and amount of tissue resected, but an increase in postoperative blood loss of 51% (284 ml versus 144 ml) [30].…”
Section: Hemorrhagic Risks In Urologic Surgerymentioning
confidence: 99%